2022
DOI: 10.17509/ijal.v12i1.46563
|View full text |Cite
|
Sign up to set email alerts
|

Genre-based teaching cycle and instructional design for teaching texts and mandated curriculum contents

Abstract: This study aimed to construct a genre-based teaching (GBT) model for accommodating the Indonesian EFL curriculum. Anchored in two current GBT cycles developed by Derewianka and Jones (2016) and Chappell (in preparation), a modified GBT cycle and the following instructional design model were constructed. This design-based study conducted its first two stages: the analysis of practical problems and the development of solutions based on the existing knowledge. The practical problem analysis was executed through f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…The findings corroborate the previous studies suggesting the need to include culture in Indonesian textbooks, among others Faris (2014), Sulistiyo et al (2021), and Syahri and Susanti (2016). Particularly, the current study confirms the earlier studies (Faris, 2014;Sulistiyo et al, 2021;Syahri & Susanti, 2016;Triastuti et al, 2022) as part of Indonesian cultures to learn and put more emphasis on the local cultures than the international and target cultures. The findings of this study corroborate the previous studies suggesting the need to include culture in Indonesian textbooks, such as those of others Faris (2014), Sulistiyo et al (2021), andSyahri andSusanti (2016).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings corroborate the previous studies suggesting the need to include culture in Indonesian textbooks, among others Faris (2014), Sulistiyo et al (2021), and Syahri and Susanti (2016). Particularly, the current study confirms the earlier studies (Faris, 2014;Sulistiyo et al, 2021;Syahri & Susanti, 2016;Triastuti et al, 2022) as part of Indonesian cultures to learn and put more emphasis on the local cultures than the international and target cultures. The findings of this study corroborate the previous studies suggesting the need to include culture in Indonesian textbooks, such as those of others Faris (2014), Sulistiyo et al (2021), andSyahri andSusanti (2016).…”
Section: Discussionsupporting
confidence: 92%
“…The findings of this study corroborate the previous studies suggesting the need to include culture in Indonesian textbooks, such as those of others Faris (2014), Sulistiyo et al (2021), andSyahri andSusanti (2016). In particular, the current study confirms the earlier studies (Faris, 2014;Sulistiyo et al, 2021;Syahri & Susanti, 2016;Triastuti et al, 2022) which suggested the need to promote local culture in the textbooks, in addition to the culture from the target language, i.e. English.…”
Section: Discussionsupporting
confidence: 90%
“…This approach is referred to as text-based teaching. However, in practice, the implementation of text-based teaching in Indonesia has raised several issues (Triastuti, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of genre-based language teaching is to build competence for performing social functions by using texts with structures and linguistic elements that are appropriate to the communicative purpose and context. The implementation of the Genre-Based Approach in curriculums has been recommended in several studies, including by Rivera (2012); Abbaszadeh (2013);and Triastuti et al, (2022). Many studies have found that the Genre-Based Approach is suitable for improving students' understanding of texts and their production of written and spoken texts (Elshirbini & Elashri, 2013;Ningsih, 2015;Nahid et al, 2018;and Herman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%